Mechano-regulation of the beating heart at the cellular level - Mechanosensitive channels in normal and diseased heart - Friedrich, Oliver; Wagner, Sören; Battle, Andrew; Schürmann, Sebastian; Martinac, Boris (Progress in Biophysics & Molecular Biology, 2012)
The heart as a contractile hollow organ finely tunes mechanical parameters such as stroke volume, stroke pressure and cardiac output according to filling volumes, filling pressures via intrinsic and neuronal routes. At the cellular level, cardiomyocytes in beating hearts are exposed to large mechanical stress during successive heart beats. Although the mechanisms of excitation-contraction coupling are well established in mammalian heart cells, the putative contribution of mechanosensitive channels to Ca homeostasis, Ca signaling and force generation has been primarily investigated in relation to heart disease states. For instance, transient receptor potential channels (TRPs) are up-regulated in animal models of congestive heart failure or hypertension models and seem to play a vital role in pathological Ca overload to cardiomyocytes, thus aggravating the pathology of disease at the cellular level. Apart from that, the contribution of mechanosensitive channels (MsC) in the normal beating heart to the downstream force activation cascade has not been addressed. We present an overview of the current literature and concepts of mechanosensitive channel involvement in failing hearts and cardiomyopathies and novel data showing a likely contribution of Ca influx via mechanosensitive channels in beating normal cardiomyocytes during systolic shortening. © 2012 Elsevier Ltd.
Keywords: Calcium homeostasis; Cardiomyocytes; Heartbeat; Mechanosensitive channel; Transient receptor potential channel